A tutela penal da mulher: histórico, limites e exigências para uma proteção eficiente - Santos, Silvia Chakian de Toledo (2018)
This work aims to study the evolution of the applicability of Criminal Law to women‟s protection, since the first law sources until the present moment, in order to identify the requirements of building a contemporary criminal law model, within a feminist paradigm. I argue that such model is only possible through the comprehension of the historical aspects (the several discourses that contributed to the construction of feminine inferiority) and the great transformations that allowed the change of standarts, as the woman is presently regarded as a right-holder. This scenery at the same time instantiate the limits of Criminal Law and provide the guidelines that fulfil the ideal of efficience. Therefore, the social-historical construction of women‟s inferiority is analyzed through its several conceptions (from the Christian mistyque, during the Middle Age, the medical literature and psychoanalisys discourse, philosophy, the liberal post-revolution models and Brazilian‟s colonial period until the present republican era). This rendering highlights factors and values that guided the production of a Law, in Western and Brasilian scope, where the criminal law applicability on behalf of woman is restricted to the concern with her chastity, virginity, modesty, sexual honesty, marital honor and succession matters. Based on Miguel Reale‟s three-dimensionalism, here approached in a critical and contemporary perspective, we analyze the main transformations that provide axiologial substract for claiming the creation of a new Law, in Brazil and around the world: the paradigm of human dignity and the feminist thought; the latter supporting the study of the categories patriarchy, gender and violence against women. This new standard grounds the analysis of the claims for new protection apparatuses, in international level, where Treaties, Conventions and Declaration of Women Human Rights‟ Protection are analyzed; the constitutional level, where we approach the principle of human dignity, the equality and positive discrimination on 1988‟s Brazilian Federal Constitution, together with the participation of women during the Constituint Assembly; and infraconstitutional level, where we examine the most important laws that had altered the 1940‟s Criminal Code after 1988 (Law 10.224/01 – sexual harassment; Law 11.106/05 and Law 12.015/09 – sexual offences, Law 13.718/18, Law 11.340/06 - Law Maria da Penha, and Law 13.104/15 – Feminicyde Law). Lastly, the search of guidelines to creating an efficient protection model is guided by the notion of total criminal science, which, we argue, requires the contribution of a feminist criminology (or a feminist perspective), as well as the adoption of other strategies, beyond the criminal approach, specially the network efforts and the incorporation of a gender perspective in the application of the Law